Representaciones y beneficencia. Mujeres alemanas y judías en Argentina, siglo XX - de Chervonagura, Elisa Cohen; Lupprich, Edith (Diálogos Latinoamericanos, 2014)
Recently, historical and migration studies have started to pick up the multiple contributions of native and immigrant women to the construction of the Argentinian nation, especially by their participation in welfare, political and union associations. In this paper, we look into two groups of women, Jewish and German women in Argentina. We focus on three texts about German immigration to Argentina, with the aim to find out which is the discursive representation of women in these texts, which properties and activities are predicated about them, and to which extend they appear with independence of other (male) family members. We detect that two texts support a 'traditional' representation, where women stay in the background and have hardly any function with independence of their husbands or teachers. The third text partly presents the same traits, whereas in other opportunities it highlights female achievements.